2015
DOI: 10.1186/s12879-015-0831-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of the molecular vaginal microbiota composition of African women

Abstract: BackgroundSociodemographic, behavioral and clinical correlates of the vaginal microbiome (VMB) as characterized by molecular methods have not been adequately studied. VMB dominated by bacteria other than lactobacilli may cause inflammation, which may facilitate HIV acquisition and other adverse reproductive health outcomes.MethodsWe characterized the VMB of women in Kenya, Rwanda, South Africa and Tanzania (KRST) using a 16S rDNA phylogenetic microarray. Cytokines were quantified in cervicovaginal lavages. Pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 36 publications
11
44
0
Order By: Relevance
“…Supporting these results, it has also been reported in other studies about the composition of species in the vaginal microbiome of black and white women born in the US, a significant difference between these two groups, in which black women have a greater microbial diversity and a lower probability of lactobacilli colonization than white women [24,79]. In other studies, conducted in sub-Saharan African countries, a smaller proportion of L. crispatus in the vaginal communities compared to women of European or Asian descent has been found [24,79,80]. Here, African communities were dominated by L. iners and by a variable mixture of facultative anaerobic bacteria [24,68,81].…”
Section: Ethnicitysupporting
confidence: 60%
“…Supporting these results, it has also been reported in other studies about the composition of species in the vaginal microbiome of black and white women born in the US, a significant difference between these two groups, in which black women have a greater microbial diversity and a lower probability of lactobacilli colonization than white women [24,79]. In other studies, conducted in sub-Saharan African countries, a smaller proportion of L. crispatus in the vaginal communities compared to women of European or Asian descent has been found [24,79,80]. Here, African communities were dominated by L. iners and by a variable mixture of facultative anaerobic bacteria [24,68,81].…”
Section: Ethnicitysupporting
confidence: 60%
“…20 Our cytokine findings are consistent with previous studies that reported an increase of cervicovaginal pro-inflammatory cytokines in women with BV. 11,13,14 However, some cytokines that have frequently been studied in this context (such as IL-1b, IL-6, and IL-8) were not identified in our study, probably due to relatively low concentrations that fall outside the dynamic range of the mass spectrometer. 41 The cytokines that we did detect (IL-36a, IL-36g, Il-36 receptor antagonist, migration inhibitory factor, glucose-6-phosphate isomerase, C5, metalloproteinase inhibitor 1) have not been studied in the context of vaginal dysbiosis before.…”
Section: Articlesmentioning
confidence: 59%
“…However, recent clinical studies have shown increased cervicovaginal fluid concentrations of the pro-inflammatory cytokines interleukin (IL)-1b and IL-8, and decreased concentrations of the antiinflammatory cytokine IL-10 and the antiproteases secretory leukocyte protease inhibitor and elafin (PI3). [9][10][11][12][13][14] Furthermore, in vitro studies have shown that lactobacilli do not generally induce human AMPs, whereas BV-associated bacteria (such as Gardnerella vaginalis, A. vaginae and P. bivia) do. 10,12 The cervicovaginal proteome has been characterized by others before, [15][16][17][18][19][20] but never in the context of different VMB compositions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010–2011, we conducted a multi-country follow-up study entitled ‘‘Characterisation of novel microbicide safety biomarkers in East and South Africa”. The main aim of that project was to characterise the vaginal microbiome and the cervicovaginal mucosal immune system in African women and to assess changes of these over time [ 18 21 ]. In that study, 430 women were recruited at three study sites, i.e.…”
Section: Methodsmentioning
confidence: 99%